Development of Career Patterns of Civil Servants in the Human Resources Staff Unit of the National Police - Syaifuddin Syaifuddin; Nurliah Nurdin; Mala Sondang Silitonga (Jurnal Ad'ministrare, 2023)
The existence of civil servants in the National Police institution is something unique and distinctive because in the National Police organization, the position of civil servants is in one organization with the National Police in all units of the National Police in charge of carrying out administrative activities and tasks that require special expertise to support the  activities of the  National Police.  For civil servants of the National   Police, personnel regulations  apply to the  National Police and  personnel regulations regulated by BKN.    The purpose of  this study is to analyze   the causes of  the lack of optimal implementation of career patterns for civil servants in the  Human Resources Staff (SSDM) of the National Police and provide a description related to career  pattern models  that are more professional and appropriate for civil servants in SSDM   Polri which can be used as a  career pattern model for National Police Civil Servants. This research uses a mix method approach,  quantitative data collection which is then deepened qualitatively through interviews, observations and collection of supporting documents. The result is that the career pattern of civil servants in the Human Resources Staff Work Unit   is constrained by human resource  management governance  in the aspects of planning,   organizing, procuring and directing, developing and integrating. A more provective career pattern model obtained from the results of discussion and analysis in this study is the placement of  civil servants in   predetermined functional and structural positions, the implementation of internships for employees who  newly recruited, implementation of performance evaluation for promotion followed by attending education and  training in accordance with the  field of work, providing space and  opportunities to  actualize themselves to the duties   and  responsibilities  that given in order to be promoted  to the top posotion intended for civil servant after attending a series of education and training for competency development.